The 4C's approach in employee relation / Campbell Apau ... [et. al] - Apau, Campbell; Giang, Carolina Sandra; Tuwet, Jaapar Sah; Santalia, Junie George; Hj Su'ut, Suria (2003)
The study on staff relationships at Everrise Departmental Store Sdn. Bhd. in Kuching, Sarawak started on November 21, 2002 and officially ended on December 31, 2002. The study took a consultative approach in that the customer's needs were first established. Then, the expectations were verbally agreed between the consultants and the client (that is, Everrise Departmental Store Sdn. Bhd.). The consultants performed an extensive organizational employee survey through the administration of a questionnaire. The number of employees surveyed was one-hundred and eighty-seven (187). This figure represented slightly more than thirty percent (30%) of the employees of Everrise in Kuching. The discussion on methodology can be found in section 5.0. The consultants decided to use the 4Cs model namely, corporate culture, commitment, communication and compensation. The rationale for using this model is explained in section 6.0. There are several limitations to the study which are discussed in the report. This report has several conclusion and recommendations in section 8.0 based on the findings presented in section 7.0. There is also a short section on proposed future works in section 9.0 should there be a need to continue with the study. The overall assessment is that there is a positive climate in staff relationships at Everrise Departmental Store Sdn. Bhd. Finally, the consultants believe that the objective of the study has been met.